Characteristics of Directive Speech Acts in the Dissemination of COVID-19 Mitigation Information in Japan - Bayu Aryanto (Japanese Research on Linguistics, Literature, and Culture, 2020)
Abstract The global conditions in the current COVID-19 pandemic have instigated the public to try and take preventive measures against the spread of the COVID-19 virus. Preventive measure in the form of information dissemination regarding the COVID-19 virus is manifested in various forms, wherein one of them is through the posting of announcements in strategic locations with the expectation that everyone has the opportunity to understand what should be done in order to prevent the spread of the virus. The current study aims to describe the characteristics of directive speech act used in the dissemination of COVID-19 mitigation information in Japan. Data were obtained from written announcements concerning COVID-19 mitigation in public areas such as train stations, bus stops, public playgrounds, shopping venues, schools, hotels, and offices. The data were taken from 30 different locations throughout Japan. Sociopragmatic study was used as a method in this research with data in the form of directive speech acts found in written announcements concerning COVID-19 mitigation. As many as 50 directive speech acts were found in various linguistic forms (teineitai form and keigo form), and they were also found to be dominated by direct directive speech. Keywords: covid-19, directive speech act, keigo, mitigation AbstrakKondisi dunia yang sedang dalam masa pandemic covid-19, membuat masyarakat berusaha melakukan tindakan pencegahan terhadap penyebaran virus covid-19. Pencegahan berupa sosialisasi mengenai virus covid-19 diwujudkan dalam banyak hal, salah satunya melalui pemasangan pengumuman-pengumuman yang dipasang di lokasi startegis dengan harapan setiap orang memiliki kesempatan untuk mengetahui apa yang harus dilakukan dalam rangka pencegahan penyebaran virus covid-19.Penelitian ini bertujuan untuk mendeksripsikan karakteristik tindak tutur direktif yang digunakan dalam sosialisasi mitigasi covid-19 di Jepang. Sumber data diambil dari pengumuman tertulis tentang mitigasi covid-19 di area public seperti stasiun, halte bis, taman bermain, tempat belanja, sekolah, hotel, dan perkantoran. Sumber data tersebut diambil dari 30 lokasi yang berbeda di Jepang. Kajian sosiopragmatik digunakan sebagai metode penelitian ini dengan data berupa tindak tutur direktif yang terdapat dalam pengumuman tertulis mitigasi covid-19. Ditemukan data tindak tutur direktif sejumlah 50 tuturan dalam berbagai ragam Bahasa (ragam teineitai dan ragam keigo) dan didominasi dengan tuturan direktif langsung. Kata Kunci: covid-19, tindak tutur direktif, keigo, mitigasi